Study of time link calibration based on GPS carrier phase observation. Issue 11 (17th September 2018) - Zhang, Pengfei; Tu, Rui; Gao, Yuping; Guang, Wei; Zhang, Rui; Cai, Hongbin
Abstract : The time link calibration of Global Positioning System (GPS) based on carrier phase observation has been performed in the past few years. However, the calibration accuracy is expected to be improved. In this paper, an approach of time link calibration for reducing the uncertainty is proposed. The mechanism and procedure for time link calibration based on GPS are investigated in depth firstly. And then GPS data processing method and strategies in calibration are discussed, where the precise time transfer solution (PTTSol) software is also developed. The experiment of zero baseline time link is employed, of which the standard deviation (STD) value of clock difference reaches 0.03 ns. The root mean square (RMS) value of clock difference in long distance time link is 0.11 ns which compared with the international GPS service (IGS) value. At last, one calibration campaign was organized at the national time service center (NTSC) from modified Julian day (MJD) 57598 to MJD 57616. With a travel receiver forming three common clock difference (CCD) modes, the estimated uncertainty of the calibration value was 0.13 ns, which neglected uncertainty of 1 pulse per second (1 PPS) signal relative to the local time reference point.